AN ANALYSIS OF STUDENTS’ DIFFICULTIES IN WRITING RESEARCH PROPOSAL - Diad, Januardi; Rezeki, Yanti Sri; Rahmani, Eka Fajar (Universitas Islam Nahdlatul Ulama Jepara, 2023)
This study aimed to analyze and identify the factors contribute to the difficulties faced by undergraduate students in writing research proposal. Descriptive research design was employed in this study. 36 undergraduate students of English Education Study Program at FKIP of Universitas Tanjungpura in Pontianak were selected as the sample by using purposive sampling. The data were collected by using questionnaire consists of 25 items adapted from Dwihandini, et al. (2013), focus on the three factors causing undergraduate students’ difficulties in writing research proposal, involving psychological factors, sociocultural factors, and linguistic factors. Data analysis indicated that psychological factors with the percentage of 61%, as the most dominant factors causing students’ difficulties in writing research proposal, linguistic factor with the percentage of 21%, and sociocultural factor with the percentage of 18%. Therefore, psychological aspects as the most influential factor causing students’ difficulties in research proposal writing.